Reducing right ventricular pacing burden: algorithms, benefits, and risks. Issue 4 (13th November 2018) - Jankelson, Lior; Bordachar, Pierre; Strik, Mark; Ploux, Sylvain; Chinitz, Larry
Abstract: Algorithms designed to reduce the burden of right ventricular pacing are widely available in modern implantable pacing devices. To ensure safe and optimal utilization, understanding the properties of these algorithms as well as their possible unfavourable effects is essential. In this review, we discuss in detail the technical and clinical aspects of rhythm management algorithms and update on their significant recent modifications. In addition, we highlight possible adverse phenomena that may be induced by these different pacing algorithms intended to minimize pacing.